Axiomatic rationality and ecological rationality. - Gigerenzer, Gerd (Synthese, 2021)
Axiomatic rationality is defined in terms of conformity to abstract axioms. Savage (The foundations of statistics, Wiley, New York, 1954) limited axiomatic rationality to small worlds (S, C), that is, situations in which the exhaustive and mutually exclusive set of future states S and their consequences C are known. Others have interpreted axiomatic rationality as a categorical norm for how human beings should reason, arguing in addition that violations would lead to real costs such as money pumps. Yet a review of the literature shows little evidence that violations are actually associated with any measurable costs. Limiting axiomatic rationality to small worlds, I propose a naturalized version of rationality for situations of intractability and uncertainty (as opposed to risk), all of which are not in (S, C). In these situations, humans can achieve their goals by relying on heuristics that may violate axiomatic rationality. The study of ecological rationality requires formal models of heuristics and an analysis of the structures of environments these can exploit. It lays the foundation of a moderate naturalism in epistemology, providing statements about heuristics we should use in a given situation. Unlike axiomatic rationality, ecological rationality can explain less-is-more effects (when using less information can be expected to generate more accurate predictions), formalize when one should move from 'is' to 'ought,' and be evaluated by goals beyond coherence, such as predictive accuracy, frugality, and efficiency. Ecological rationality can be seen as a formalization of means–end instrumentalist rationality, based on Herbert Simon's insight that rational behavior is a function of the mind and its environment.